Ethics in the knowledge organization environment: An overview of values and problems in the LIS literature - Guimarães, José Augusto Chaves [UNESP]; Fernández-Molina, Juan Carlos; Pinho, Fabio Assis [UNESP]; Milani, Suellen Oliveira [UNESP] (My University, 2008)
Reflections on Information Science have been focused mostly on information access and dissemination, not on ethical aspects of knowledge organization and representation (KOR). This leads us to investigate the existence of ethical values - and problems - which have impact on this field, especially since they are not discussed, although they are revealed in everyday practice. Therefore, and trying to contribute to a further reflection on the lack of literature on ethics in KOR, this paper analyses the Journal of the American Society for Information Science and Technology - JASIST, Journal of Documentation, Knowledge Organization, Cataloging & Classification Quarterly, The Indexer and Ethics and Information Technology in the period between 1995 and 2004. The results reveal two complementary dimensions: one concerning the respect of diversity and the other concerning the specificity warrant. The latter, which may prove the relevance of the theoretical principles announced by Hudon (1997), Beghtol (2002, 2005) and García Gutiérrez (2002), relative to a transcultural ethics of mediation that reflects diversity (fitted with a precision that, many times, passes by the dimension of multilingualism), making use of tools that may provide cultural warrant to knowledge representation.